PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA APARATUR PEMERINTAH DAERAH KOTA LANGSA - Qori Vebriani; Afrah Junita; Agustina Nurul Fajriah (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to examine the effect of budgeting participation, organizational commitment, and job satisfaction on the performance of local government officials in Langsa City. This study is a quantitative study. Consisting of 108 respondents. The population in this study was 36 OPDs in Langsa City. The sampling method used in this study was a purposive sampling technique. The analysis technique used in this study was multiple linear regression analysis processed through the IBM SPSS application. The results of the study indicate that budgeting participation has a significant effect on the performance of local government officials, organizational commitment has an effect on the performance of local government officials. However, job satisfaction has no effect on the performance of local government officials. However, simultaneously budgeting participation, organizational commitment, and job satisfaction have a significant effect on the performance of local government officials. The limitation of this study is that this study was only conducted in one local government area, namely in Langsa City, so the results cannot be generalized to other areas with different organizational conditions. Meanwhile, the suggestion in this research is that for local governments, it is important to continue to increase the involvement of apparatus in the decision-making process, especially in budget planning, in order to foster a sense of responsibility and ownership